Characterization of the macromolecular and sensory profile of non-alcoholic beers produced with various methods. (February 2019) - Krebs, Georg; Müller, Magdalena; Becker, Thomas; Gastl, Martina
Abstract: Due to changing consumer habits, non-alcoholic beer is the fastest-growing market within the beverage industry. Different processing technologies for limiting the alcohol content of beer yield in completely different matrix compositions and sensory profiles. Especially the specific sensory attributes of palate fullness, mouthfeel, and the perception of harmony (ratio harmony between sweetness and sourness) of non-alcoholic beers are often described as atypical and unbalanced by the consumer. In addition to technological aspects, the matrix components represent a significant factor. Cereal-based beverages contain a complex mixture of various polymers that includes proteins, polyphenols, and polysaccharides. These polymers affect the sensory perception of beverages in terms of mouthfeel depending on their substance properties. This article reports the analytical characterization of the macromolecular profile of non-alcoholic beers to predict sensory differences in palate fullness and mouthfeel that arise because of variations in polymer profile and processing method. Therefore, asymmetric flow-field-flow-fractionation (FFF/AF4), multi-angle light-scattering (MALS), and refractive index measurements were used to characterize polymers in non-alcoholic beers. We observed significant differences in the ratio of low- to high-molar-mass polymers. These differences included a shift of the molar mass distribution towards higher molar masses for beers subjected to higher thermal loads during dealcoholization in a rectification column. Limited fermentation beers tended to be composed of more low-molar-mass polymers. Highly discriminating sensorial assessment schemes demonstrate the correlations between differences in macromolecular profile and specific sensory impressions like sweetness (basic taste), palate fullness and harmony . This trend is verified in the present study with spiking experiments using substances that are known to influence mouthfeel and palate fullness, such as beta-glucans, dextrins, isomaltulose, and other low-molar-mass sugars, may be controlled during the production process. These results confirm that the particular sensory attributes can be influenced by different classes of cereal-based substances, especially by varying their molar mass fractions and concentrations. Maltodextrins and β-glucan are shown to enhance palate fullness. Spiking with maltodextrin caused a lasting, smooth, and pleasant perception of mouthfeel; spiking with β-glucan resulted in a more viscous, thick perceived mouthfeel. However, spiking with isomaltulose led solely to a sweet taste (basic taste). These tests show more generally that AF4-MALS is a suitable analytical tool for understanding how the macromolecular fractions in cereal-based beverages are linked to sensory impressions. This type of assessment can be used to target the composition of polymer profiles, which can be a technological possibility to produce sensorily appealing high-quality non-alcoholic beers. Graphical abstract: Unlabelled Image Highlights: Macromolecules in nonalcoholic beers are characterized by AF4/MALS/dRI Limited-fermentation beers have lower concentrations of polymers with lower molar mass Thermally dealcoholized beers with higher polymer-concentration and higher molar mass Correlation of specific polymers or molar mass fractions to sensory attributes